Mindfulness dan Health Anxiety pada Individu Dewasa Awal - Iona Ordelia Liugiarto; Venie Viktoria Rondang Maulina (Jurnal Online Psikogenesis, 2025)
Early adulthood is when people start thinking more about health because they’re becoming more vulnerable to chronic diseases and mental health issues. With the increasing availability of health information, some individuals tend to believe the circulating information and assume they have health problems, which leads to health anxiety. Mindfulness, however, is one approach that can reduce the level of health anxiety in early adults since it helps lower distress and negative feelings. This study focuses on trait mindfulness, which reflects the level of mindfulness in a person’s daily life. The aim of this study is to explore the relationship between mindfulness and health anxiety in early adulthood. This research used a quantitative approach with a correlational design. The participants were early adults aged 18–25 years living in Jabodetabek, with a total of 202 participants collected through convenience sampling. The instruments used were the Five Facet Mindfulness Questionnaire (FFMQ) and the Short Health Anxiety Inventory (SHAI). Data were analyzed using Spearman correlation. The results showed a negative correlation between mindfulness and health anxiety, meaning that higher mindfulness is linked to lower health anxiety, and vice versa. Keywords: mindfulness, health anxiety, early adulthood